A novel single-element transducer with curved surface for cavitation detection. Issue 1 (May 2021) - Yin, Xiaoyu
Abstract: Acoustic cavitation is increasingly used to apply in industrial and clinical areas. However, with the development of these fields, the precision of devices used to monitor cavitation activity gradually cannot meet the needs of the higher accuracy requirements of practical application. In this paper, we propose several design schemes of a novel passive cavitation detector (PCD) which is hoped to have better measuring performance than traditional plane PCD because of its focusing effect. By conducting FEM simulations, the optimal design plan and the surface curvature of PCD were chosen. It is shown that the measuring ability of the final selected PCD is near 1.7 times of traditional plane PCD.